2019
DOI: 10.1002/celc.201801677
|View full text |Cite
|
Sign up to set email alerts
|

Landfill Leachate Treatment by Combining Coagulation and Advanced Electrochemical Oxidation Techniques

Abstract: This paper presents and discusses the results obtained in the treatment of raw landfill leachate (RLL) with a combination of coagulation-flocculation (Alum) and electrochemical techniques, using a filter-press reactor with a boron-doped diamond electrode. The success of the treatment was demonstrated by the quality of the treated water, which was evaluated based on parameters such as color, odor, turbidity, chemical oxygen demand, biochemical oxygen demand, free and total chlorine, total nitrite and nitrate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Several studies investigated the performance of EO to remove common wastewater parameters form landfill leachate (LL). For instance, Panizza et al [2] successfully removed chemical oxygen demand (COD) from LL to below the disposal limit (160 mg L −1 ) and de Oliveira et al [3] reported a COD removal of 90% or higher. Satisfactory removal of ammonium nitrogen (NH 3 -N) from LL of up to 100% by EO has been reported by Li et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the performance of EO to remove common wastewater parameters form landfill leachate (LL). For instance, Panizza et al [2] successfully removed chemical oxygen demand (COD) from LL to below the disposal limit (160 mg L −1 ) and de Oliveira et al [3] reported a COD removal of 90% or higher. Satisfactory removal of ammonium nitrogen (NH 3 -N) from LL of up to 100% by EO has been reported by Li et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the advanced oxidation processes, the electro-oxidation (EO) process is an effective process that can be applied at standard conditions. Recently, applications of advanced EO processes have drawn attention especially in the removal of resistant organic compounds [11][12][13]. The EO processes are based on in situ electrogeneration of hydroxyl radicals, which is a strong oxidant that does not show selective behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are combined process applications as well as stand-alone EO processes in leachate treatment. The other component of the combined processes in which EO is applied as pre or post-treatment can be biological, physical, or chemical applications [13,[30][31][32]. In the study conducted by Gilvapas et al [30], the coagulation process was applied before the EO process using BDD anode, and 93.5% COD removal efficiency was obtained.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations